Deriving the internal bony structure of the cochlea from high-resolution µCT images for translation to low resolution image-based construction of person-specific computational models of cochlear implants - Hanekom, Tania (University of Pretoria, 2020)
Thesis (PhD (Biosystems))--University of Pretoria, 2019.